Scalable Trust Management model for Machine To Machine communication in Internet of Things using Fuzzy approach (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Revolution in Machine to Machine (M2M) Communication in Internet of Things (IoT) provides smart services in all verticals. These smart heterogeneous devices can be constraint or powerful devices that are generating sensitive information and introducing new challenges in security, privacy, and trust in devices to get and provide services in a distributed fashion. These challenges are overcome by providing scalable decentralized trust management for the access control system. Trust-based security models are more reliable over cryptographic security to identify and mitigate different inside threats by assessing the trust scores. This paper proposed Scalable Trust Management (STM) using a fuzzy approach and parameters like Experience, Recommendation, and device classification are used to calculate the crisp value of the trust score. While designing rule for trust score capacity of device is considered. The simulation of STM in NS2 ensures good performance and its result guarantees scalability and energy efficiency in the heterogeneous network.